Pemberdayaan Mahasiswa Melalui Edukasi Stunting Berbasis Poster Edukatif Pada Ibu Balita Di Beberapa Desa Kabupaten Semarang - Farah Bidara (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Stunting is a chronic nutritional problem that adversely affects children's physical growth, cognitive development, and the quality of human resources in the future. Efforts to prevent stunting require the involvement of multiple stakeholders, including higher education institutions through community service programs. Students of the Early Childhood Islamic Education (PIAUD) Study Program have the potential to serve as community empowerment agents by improving family health literacy through educational activities. This community service program aimed to improve mothers' understanding of stunting through poster-based educational activities designed and presented by PIAUD students. This community service program employed a health education approach using participatory, interactive counseling supported by poster media. The program held in June 2026 involved 24 students from the Early Childhood Islamic Education (PIAUD) Study Program at Universitas Islam Negeri Salatiga as educational facilitators and 75 mothers with children under five years of age from several villages in Semarang Regency as participants. The program consisted of preparation, poster development, educational sessions, interactive discussions, and reflection. The students successfully developed educational posters on stunting and delivered the educational materials through interactive presentations. Participants demonstrated high enthusiasm throughout the activity, as reflected by their active participation in discussions and question-and-answer sessions regarding the causes, impacts, risk factors, and prevention of stunting. The program also enhanced students' learning experiences in delivering health education to the community and strengthened their role as community empowerment agents.